Guide to Supply Chain Management - Scott, Colin (Springer Berlin Heidelberg, 2011)
This guide brings supply chain theory to life. Written for people with a business interest in supply chain management, the book covers the key topics in eleven chapters, including plan, source, make, deliver and return as well as strategy, people, finance, customer service and outsourcing. Each chapter starts with a brief summary and learning objectives that guide the reader through the text. The book is written in a clear and simple way, featuring a variety of figures, tables and recommended further readings. The chapters conclude with real-life case studies for best practice. During their work, the authors have met professionals all over the world who are passionate about their business achievements. By including their vivid examples, the guide brings theory to life enabling readers to understand the concepts and ideas presented in the guide. Colin Scott, Henriette Lundgren and Paul Thompson are experts in supply chain management and have worked with practitioners in businesses across the globe. "This guide is a really useful reminder of what good practice is and how it should be applied within supply chain management. The book is relevant for students of supply chain management and professional practitioners alike. This book offers an invaluable guide to understanding the specific dynamics of your supply chain and the fundamentals underpinning it. It provides the framework for delivering a supply chain strategy based upon recognised best practice." Martin McCourt, CEO, Dyson Limited